2010
DOI: 10.1007/s00204-010-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer effects of formaldehyde: a proposal for an indoor air guideline value

Abstract: Formaldehyde is a ubiquitous indoor air pollutant that is classified as “Carcinogenic to humans (Group 1)” (IARC, Formaldehyde, 2-butoxyethanol and 1-tert-butoxypropanol-2-ol. IARC monographs on the evaluation of carcinogenic risks to humans, vol 88. World Health Organization, Lyon, pp 39–325, 2006). For nasal cancer in rats, the exposure–response relationship is highly non-linear, supporting a no-observed-adverse-effect level (NOAEL) that allows setting a guideline value. Epidemiological studies reported no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(106 citation statements)
references
References 103 publications
6
96
0
Order By: Relevance
“…3,7,19,22 Many institutions and government regulations have considered it to be a carcinogenic agent. 3,5,7,10,11,15,19,22 Although formaldehyde is still needed to prevent microorganism growth (especially fungi), formaldehyde content in the customized embalming fluid described here was almost 80% less than in a conventional formaldehyde mixture. Furthermore, customized specimens provided a less aggressive and contaminated environment than the formaldehyde and cryopreserved specimens.…”
Section: Biohazard Risk and Health Standardsmentioning
confidence: 85%
See 1 more Smart Citation
“…3,7,19,22 Many institutions and government regulations have considered it to be a carcinogenic agent. 3,5,7,10,11,15,19,22 Although formaldehyde is still needed to prevent microorganism growth (especially fungi), formaldehyde content in the customized embalming fluid described here was almost 80% less than in a conventional formaldehyde mixture. Furthermore, customized specimens provided a less aggressive and contaminated environment than the formaldehyde and cryopreserved specimens.…”
Section: Biohazard Risk and Health Standardsmentioning
confidence: 85%
“…Additionally, many studies have reported that long-term exposure to high airborne formaldehyde concentrations in the laboratory is hazardous. 6,9,10,11,15 In 2006, the International Agency for Research on Cancer (IARC) 22 and the US Environmental Protection Agency 19 classified formaldehyde as a probable human carcinogen.…”
mentioning
confidence: 99%
“…48 Nasal epithelia is commonly represented by 75% of columnar surface epithelium, 14% of other epithelial cells, 11% of neutrophils, 0.07% of eosinophils and 0.2% lymphocytes. Apart from the potential value of the nasal epithelial cells for the prediction of cancer risk of the respiratory tract, 16,27 the use of nasal epithelia may allow mechanistic studies of various carcinogens, including those contained in tobacco smoke, 16,39 industrial air pollution, [20][21][22]28 and hair-dyeing.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen oxides (particularly NO, NO 2 , and N 2 O 3 ) in tobacco smoke can be anticipated to contribute to enhanced protein nitrosylation (S-nitrosylation), a key post-translation modification that frequently targets apoptotic and prosurvival proteins such as Ras, caspases, and IKKb (1, 2). Cigarette smoke also contains oxidants (including formaldehyde) that are implicated in carcinogenesis (33,34).…”
Section: Discussionmentioning
confidence: 99%